Enactivism and neonatal imitation: conceptual and empirical considerations and clarifications - Lodder, Paul; Rotteveel, Mark; van Elk, Michiel (Frontiers in Psychology, 2014)
Recently within social cognition it has been argued that understanding others is primarily characterised by dynamic and second person interactive processes, rather than by taking a third person observational stance. Within this enactivist view of intersubjective understanding, researchers differ in their claims regarding the innateness of such processes. Here we proposed to distinguish nativist enactivists - who argue that studies on neonatal imitation support the view that infants already have a non-mentalistic embodied form of intersubjective understanding present at birth - from empiricist enactivists, who claim that those intersubjective processes are learned through social interaction. In this article, we critically examine the empirical studies on neonate imitation and conclude that the available evidence is at least mixed for most types of specific gesture imitations. In the end, only the tongue protrusion imitation appears to be consistent across different studies. If neonates imitate only one single gesture, then a more parsimonious explanation for the tongue protrusion effect could be put forward. Consequently, the nativist enactivist claim that understanding others depends on second person interactive processes already present at birth seems no longer plausible. Although other strands of evidence provide converging evidence for the importance of intersubjective processes in adult social cognition, the available evidence on neonatal imitation calls for a more careful view on the innateness of such processes and suggests that this way of interacting needs to be learned over time. Therefore the available empirical evidence on neonate imitation is in our view compatible with the empiricist enactivist position, but not with the nativist enactivist position.